Online equivalent series resistance estimation method for condition monitoring of DC-link capacitors - Sundararajan Prasanth (2018)
In this paper, a cost-effective and reliable equivalent series resistance (ESR) estimation method for aluminium electrolytic capacitors used as DC-link capacitors in front-end rectifier fed inverters is proposed. The proposed method is based on the extraction of switching frequency components of DC-link voltage and current using band-pass filters. A limiting value of switching frequency is identified, below which a new solution is proposed to achieve higher accuracy compared to the similar methods using band-pass filters. The proposed method is verified by both simulation and experimental results and it is shown that the estimation error is very low so that this method can be used for condition monitoring of DC-link capacitors.